Sequence analysis of the VP7 gene of human rotaviruses G2 and G4 isolated in Japan, China, Thailand, and Vietnam during 2001-2003 - Quang Duy Trinh (2018)
Sequence and phylogenetic analyses of the rotavirus VP7 gene were performed on 52 human G2 and G4 strains isolated in Japan, China, Thailand, and Vietnam during 2001-2003. All genotype G2 strains included in the study clustered into lineage II of the phylogenetic tree, together with the majority of global G2 strains detected since 1995. The amino acid substitution at position 96 from aspartic acid to asparagine was noted among the emerging or re-emerging G2 rotavirus strains in Japan, Thailand, and Vietnam during 2002-2003. Genotype G4 strains detected in Vietnam grouped into lineage Ia of the phylogenetic tree, whereas Japanese G4 strains clustered in lineage Ic which included emerging G4 strains from Argentina, Italy, Paraguay, and Uruguay. It is noteworthy that an insertion of asparagine was found at position 76 in all the Japanese strains and that its presence might be involved in the emergence of G4 rotavirus in Japan during 2002-2003. © 2010 Wiley-Liss, Inc.